Dividend Policy as a Moderating of the Effect of Dividend Announcement on Stock Price in Indonesian Firms - Manurung, Adler Haymans; Machdar, Nera Marinda; FoEh, John Edward Harly Jacob; Sinaga, Jhonni (International Journal of Economics and Financial Issues, 2024)
This goal of this study is to investigate how dividend announcements affect the stock price of the company on the cum and ex-dividend dates. This study also explores the possibility of dividend policy reduce the effect of dividend announcements on stock prices on the cum and ex-dividend dates. The researcher used the unit analysis of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period of 2013 - 2018. The 2019 - 2021 period is not observed due to the present of Covid Pandemic. The findings are that the dividend announcements at cum and ex-dividend dates have positive impact on stock prices. Dividend policy weakens the impact of dividend announcements on stock prices at cum and ex-dividend dates. The dividend announcement at cum and ex-dividend dates varies across companies. This study does not use the event study method. This study has a significant implication, not only for business officials and policy makers but also for investors who directly decide how to plan their portfolio in the future as consideration in making investment decisions. There is no research in Indonesia that moderates dividend policy for the effect of dividend announcements on the cum and ex-dividend dates on stock prices, so a descriptive study is required to fill this gap.